2006
DOI: 10.1016/j.neuroimage.2006.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Orienting attention to semantic categories

Abstract: We investigated the ability to orient attention to a complex, non-perceptual attribute of stimuli—semantic category. Behavioral consequences and neural correlates of semantic orienting were revealed and compared with those of spatial orienting, using event-related functional magnetic-resonance imaging. Semantic orienting significantly shortened response times to identify word stimuli, showing that it is possible to focus attention on non-perceptual attributes of stimuli to enhance behavioral performance. Seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 60 publications
13
60
0
1
Order By: Relevance
“…For example, Egner et al (2008) manipulated the validity of cues in a cue-target paradigm and found that more informative cues evoked higher activity in fronto-parietal regions, not only when cues informed about a future location, but also when they informed about a specific visual feature of the tobe presented item. Similarly, Cristescu et al (2006) studied responses to cues that predicted either the semantic category of a to-be-presented word or its spatial location, and the authors identified a similar network to that reported by Egner et al (2008), with greater activity for diagnostic cues. M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 81%
“…For example, Egner et al (2008) manipulated the validity of cues in a cue-target paradigm and found that more informative cues evoked higher activity in fronto-parietal regions, not only when cues informed about a future location, but also when they informed about a specific visual feature of the tobe presented item. Similarly, Cristescu et al (2006) studied responses to cues that predicted either the semantic category of a to-be-presented word or its spatial location, and the authors identified a similar network to that reported by Egner et al (2008), with greater activity for diagnostic cues. M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 81%
“…The engagement of this frontal-parietal oculomotor network in orienting, together with other task-appropriate areas, has been observed in a variety of spatial and nonspatial orienting tasks, including orienting to semantic categories (Cristescu et al, 2006) and to scenes in long-term (Summerfield et al, 2006) or working memory (Lepsien et al, 2005). The activations in each task com- Figure 3.…”
Section: Shared and Task-biased Activity In The Cortexmentioning
confidence: 99%
“…There are some consistencies in the localization of such hemodynamic response enhancement reported in semantic priming paradigms: for example, several studies have reported response enhancement within parietal cortices (BAs 40 and 7) (Kotz, et al 2002;Raposo, et al 2006;Rossell, et al 2003;Wible, et al 2006). This is interesting because such regions constitute part of an attentional circuitry (Behrmann, et al 2004;Chein, et al 2003;Cristescu, et al 2006) that may be specifically engaged as participants attempt to match semantic associations and common semantic features between prime and target after both have been recognized.…”
Section: Implicit Semantic Processingmentioning
confidence: 99%
“…Indeed, there is evidence that some of these functions may be related. For example, in addition to its known role in spatial attention (Corbetta and Shulman 2002), the left parietal cortex is recruited when participants are specifically cued to attend to semantic attributes of a word target (Cristescu, et al 2006). …”
Section: Hemodynamic Response Enhancementmentioning
confidence: 99%